Bioactivity and nutritional quality of nutgall (Rhus semialata Murray), an underutilized fruit of Manipur - Singh, Thangjam Surchandra; Kshetri, Pintubala; Devi, Asem Kajal; Langamba, Pangambam; Tamreihao, Keishing; Singh, Heikham Naresh; Akoijam, Romila; Chongtham, Tania; Devi, Chingakham Premabati; Singh, Tensubam Basanta; Chongtham, Sonia; Devi, Yumnam Prabhabati; et al. (Frontiers in Nutrition, 2023)
The present study dealt with the quantification of nutritional quality and deciphering the bioactivity of Nutgall (Rhus semialata Murray syn. Rhus chinensis Mill., Anacardiaceae), an underutilized fruit crop mainly found in foothill tracks of Eastern Himalaya, India, China, Japan, Korea and other South East Asian countries. The fruit was rich in essential fatty acids. The presence of linoleic and oleic acids along with traces of docosahexaenoic acid and eicosapantaenoic acid revealed the potential food value of the fruit. 59.18% of the total amino acid composition of the protein present was constituted by essential amino acids. The EC50 value of methanolic extract (MExt) and Water extract (WExt) of the fruit were recorded as 4.05±0.22 and 4.45±0.16 µg/mL, respectively in DPPH assay and 5.43±0.37 and 11.36±2.9 µg/mL, respectively in ABTS assay as compared to Ascorbic acid (3 and 5.4 µg/mL in DPPH and ABTS assay, respectively). The CUPRAC assay also showed a high antioxidant potential of MExt and WExt (1143.84±88.34 and 456.53±30.02 mg Ascorbic Acid Equivalent/g, respectively). MExt and WExt of the fruit were more active against α-glucosidase (IC50 of 1.61±0.34 and 7.74±0.54 µg/mL, respectively) than α-amylase enzyme (IC50 14.15±0.57 and 123.33±14.7 µg/mL, respectively). In addition, the methanolic fruit extract showed low to moderate pharmacological potential in terms of antihypertensive (Angiotensin converting enzyme-I inhibition), hyperuricemia (xanthine oxidase inhibition), anti-tyrosinase, and antimicrobial activity. The IC50 values of angiotensin-converting enzyme I inhibition, xanthine oxidase inhibition and tyrosinase inhibition were recorded as 13.35±1.21 mg/mL, 93.16±4.65 mg/mL and 862.7±12.62 µg/mL respectively. The study evidently indicates that Nutgall fruit is a potential source of phytonutrients, bestowed with commercially exploitable multifaceted health benefits.